Selling Shaker : the Commodification of Shaker Design in the Twentieth Century. - Bowe, Stephen (Value: Art: Politics, 1., 2006)
The Shakers a religious community whose origins are founded in the eighteenth century continue to exert an influence upon twenty-first century life, not for their religious teachings but rather through the simple yet elegant aesthetic they developed for the everyday artefacts they designed for themselves. Selling Shaker explores this influence and charts its evolution throughout the course of the twentieth century via the interest shown by the media, art institutions and general public in the Shaker story. While other books have sought to examine the origins of the religious or aesthetic b.